From deserts the prophets come : the creative spirit in Australia : 1788-1972 - Serle, Geoffrey (Monash classics., 2014)
In the early 1970s, Geoffrey Searle presented a series of groundbreaking lectures on Australian cultural history. These lectures became the book From Deserts the Prophets Come, first published in 1973. Searle relates in his preface to the original edition, ""I was aiming to cut a new path for teaching and research in Australian history, to bring cultural history into the general discourse of Australian historians, and to bridge the gap between general history and the major works in literary, art, musical, and architectural history which have appeared in recent years."" Searle's articulation of.